2021
DOI: 10.1111/dth.15278
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's sarcoma, biologics and small molecules: Navigating the complex interplay between host immunity and viral biology. A case series with focused review of the literature

Abstract: The consequences of cytokine-specific immune modulation in the development and course of Kaposi's sarcoma (KS) are poorly understood. A retrospective chart review of patients treated with biologic/small molecule drugs and followed at the dedicated KS outpatient service of our Dermatology Unit was performed. The literature on biologic and small molecule drug use in KS patients was also reviewed. Data concerning 12 KS patients treated with biologic/small molecule drugs were collected. After a median delay of 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
2
0
2
Order By: Relevance
“…Clinically, it is presented with persistent fever, KS lesions exacerbation, edema, anemia, thrombocytopenia, and hypoalbuminemia, with a mortality rate of 60% [ 44 , 45 ]. According to this, in vitro studies have reported a relationship between the increased production of proinflammatory cytokines like TNF and the progression of KS [ 46 ]; however, it has been suggested that in vivo , TNF’s role in KS is complex and ambiguous [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, it is presented with persistent fever, KS lesions exacerbation, edema, anemia, thrombocytopenia, and hypoalbuminemia, with a mortality rate of 60% [ 44 , 45 ]. According to this, in vitro studies have reported a relationship between the increased production of proinflammatory cytokines like TNF and the progression of KS [ 46 ]; however, it has been suggested that in vivo , TNF’s role in KS is complex and ambiguous [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been proposed that PLWH have increased soluble TNF levels when they develop an exacerbated immune response [ 23 ]. However, understanding the TNF/TNFR’s axis role in KS is complex and still confusing [ 24 , 25 ]. Moreover, here is essential to mention that both TNF and TNFRs can be found in transmembrane (tm) or soluble (sol) form, and according to the form, they mediate a broad spectrum of cell functions from cell death to survival [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unter Berücksichtigung einer zusätzlich durchgeführten Literaturrecherche kam die Arbeitsgruppe zu dem Ergebnis, dass Rituximab, Infliximab (sowie andere TNF‐α‐Inhibitoren) und Ruxolitinib das Risiko für ein Rezidiv oder Neuauftreten eines KS erhöhen, während Tocilizumab und Ustekinumab einen eher neutralen Effekt zu haben scheinen. Zu Vedolizumab, Apremilast, Mirikizumab und Abatacept konnten aufgrund limitierter und teils widersprüchlicher Evidenz keine eindeutigen Schlussfolgerungen gezogen werden 2 …”
Section: Kommentarunclassified
“…Bei drei Patienten, die Vedolizumab (n = 1) oder Tocilizumab (n = 2) erhielten, beeinflusste die Biologika‐Therapie den Verlauf eines bereits bestehenden KS nicht. Therapeutisch konnte bei allen Patienten durch Absetzen des auslösenden Medikamentes allein oder in Kombination mit einer lokalen Therapie oder Chemotherapie eine anhaltende komplette Remission erreicht werden 2 . Unter Berücksichtigung einer zusätzlich durchgeführten Literaturrecherche kam die Arbeitsgruppe zu dem Ergebnis, dass Rituximab, Infliximab (sowie andere TNF‐α‐Inhibitoren) und Ruxolitinib das Risiko für ein Rezidiv oder Neuauftreten eines KS erhöhen, während Tocilizumab und Ustekinumab einen eher neutralen Effekt zu haben scheinen.…”
Section: Kommentarunclassified